Classification of Non-International Armed Conflicts S : Lessons from the Sierra Leone Conflict - Probert, Thomas (University of Pretoria, 2024)
Dissertation (LLM (International Humanitarian Law and Human Rights in Military Operations))--University of Pretoria, 2023.